Does cognitive behaviour therapy affect peripheral inflammation of depression? A protocol for the systematic review and meta-analysis - Jie Liu; Bing Cao; Ruonan Li; Ling Ding; Jiatong Xu; Haijing Ma; Jian Xue (BMJ Open)
Introduction Cognitive–behavioural therapy (CBT) is becoming the most commonly implemented and standard treatment for depression. Up to date, only a few numbers of studies have investigated the potential relationship between CBT and the change of inflammatory biomarkers in individuals of depression. And the results are inconsistent among studies. The current study aims to provide a comprehensive, systematic review of the association between CBT and changes of peripheral inflammation of individuals with depression, and clarify the alterations of inflammatory cytokines pre-CBT and post-CBT treatment by meta-analysis, anti-inflammatory.Methods and analysis This study will be conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic search of predetermined terms will be conducted with electronic databases of CENTRAL, MEDLINE, EMBASE and PsycINFO from inception to July 2021. Database searches will be supplemented by expert contact, reference and citation checking, and grey literature. Primary outcomes of interest will be validated measures for levels of inflammatory cytokines pre-CBT and post- CBT treatment in individuals with depression. Hedges’ g will be used to represent the effect size.Systematic review registration The protocol of current meta-analysis has been registered at the Open Science Framework (https://doi.org/10.17605/osf.io/tr9yh).Ethics and dissemination Formal ethical approval is not required by the National Ethical Review Board in China as primary data will not be collected. The results alterations of peripheral inflammatory cytokines pre-CBT and post-CBT treatment in individuals with depression will be disseminated through a peer-reviewed publication and inform the most up-to-date evidence of the roles of CBT treatment for depression.